STUDENTS’ PERCEPTION OF ONLINE LEARNING USING QUIZIZZ.COM AS A LEARNING MEDIA IN LEARNING ENGLISH - Akhira Yuniar; Maman Suryaman (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study focuses on students' perceptions in online learning with English subjects using the learning media quizizz.com. This study uses descriptive qualitative research and uses 2 data collection instruments, which Questionnaires and Interviews. Questionnaires were conducted to find out the participants' initial responses, afterwards were further explained with interview segments to find out more about students' perceptions of the use of quizizz.com learning media in the online learning period. The results are indicated to be satisfactory after using quizizz.com learning media within a period of 4 weeks and it is estimated that the use of quizizz.com learning media can be a further recommendation to use which is proven to be effective as a learning media in the middle of online learning.